Políticas públicas e direitos de crianças e adolescentes: o papel da mídia na expansão da cidadania - Rothberg, Danilo [UNESP]; Berti, Pedro Luis Bueno (Universidade Federal de Santa Catarina (UFSC), 2010)
This paper presents results of an evaluation of the quality of the coverage of issues associated to the preservation of rights of children and adolescents in the eight main newspapers of major cities of Bauru (Sao Paulo State) administrative region, from August 2008 to March 2009. In a total of 389 assessed stories, 66% portrayed acts of legal infraction and violence with children and adolescents as victims or perpetrators, with a fragmented and superficial perspective; 34% are greater approaches about public policies aimed at the preservation of social rights. The results show the existence of a smaller number, yet significant, of stories which presented extended and more contextualized approaches. From a general view, we can point out that the contribution given by the media as a form of vigilance over the execution of public policies has been limited, which justifies the concern of demanding, from the mass media, measures to fulfill the role attributed to them by contemporaneous democracies to the strengthening of citizenship.

O artigo descreve os resultados de pesquisa que avaliou a qualidade da cobertura de assuntos ligados à preservação dos direitos da infância e adolescência nos oito principais jornais das maiores cidades da região administrativa de Bauru (SP), no período de agosto de 2008 a março de 2009. Do total de 389 matérias avaliadas, 66% noticiaram atos infracionais e de violência com crianças e adolescentes como vítimas ou agentes, com enfoque fragmentado e superficial; 34% são abordagens mais amplas sobre as políticas públicas destinadas à preservação de direitos sociais. Os resultados indicam a ocorrência de uma quantidade minoritária - ainda que significativa - de matérias que apresentaram abordagens mais completas e contextualizadas. De maneira geral, pode-se indicar que a contribuição da mídia como forma de vigilância sobre a execução das políticas públicas do setor tem sido limitada, o que justifica a preocupação de exigir, dos meios de comunicação, medidas para que cumpram a função social a eles atribuída pelas democracias contemporâneas para a expansão da cidadania.
Public policies and rights of children and adolescents: the media’s role in the citzenship expansion
Keywords: Media; Rights of children and adolescents; Journalism ethics; Newsmaking; Mídia; Direitos de crianças e adolescentes; Ética no jornalismo; Construção da notícia